GREAT EFFORT TO FIND TREASURE IN JONATHAN CAHRLES TIRTELTAUB'S NATIONAL TREASURE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - NUFIANTO, FERRY (2011)
This study concerns with the movie entitled National Treasure which is directed by Jonathan Charles Turteltaub. The analysis of this research paper is focused on the major character, Ben gates, based on structural elements and psychological perspective. In analyzing the psychological aspect, the researcher applies the theory of individual psychology proposed by Alfred Adler. This research belongs to qualitative research, which employs textual data. The textual data are taken from the movie itself as primary data source and the other materials which are related to the analysis as secondary data source. The result of the research show that firstly, the structural elements of movie present a unity. It appears in the exposition, complication, climax, and resolution of the story. Secondly, the individual psychological analysis shows the struggle of Ben gates for getting treasure.